Improving Fine Motor Skills Through Weaving Activities in Children Aged 5-6 Years at Keledang Kindergarten Loa Janan Ilir Samarinda - Tri Mukti, Novita; Liana, Heppy; Aslina, Yeni (Manajemen Pendidikan Program Doktor, 2023)
School as a formal educational institution carries out a series of planned and organized activities, including activities in the teaching and learning process in classrooms at school, directing students to gain understanding, skills, attitudes and values, all of which support student development. The success or failure of achieving educational goals depends a lot on the teaching and learning process that occurs at the learning process point in the classroom, the main factor being the students. The type of research used in this research is classroom action research (PTK). Which aims to improve fine motor skills through weaving activities. The research subjects consisted of class B4, totaling 16 students, consisting of 8 girls and 8 boys at Keledang Loa Janan Ilir Samarinda Kindergarten. The research object was to improve fine motor skills through weaving activities in Keledang Kindergarten students. The percentage is used to describe the increase in student learning outcomes from cycle I and cycle II using the formula according to Daryanto (2011: 192) namely Students who complete their studies in (times) x 100% in (divide): total number of students. in the weaving activities of students in cycle I, meeting I obtained Developing Values ​​According to Expectations (BSH) as many as 3 students and meeting II obtained Developing Values ​​According to Expectations (BSH) as many as 7 students and meeting III was still the same as meeting II with Developing Values ​​According to Expectations (BSH) as many as 7 Students. In cycle II, meeting I obtained Developing Values ​​According to Expectations (BSH) of 8 students and meeting II obtained Developing Values ​​According to Expectations (BSH) of 11 students and meeting III obtained Developing Values ​​According to Expectations (BSH) of 14 students. The graph of the increase in student weaving activities at the Keledang Loa Janan Ilir Samarinda Kindergarten from February and March from cycle I to Cycle II. Weaving activities using origami paper in the B4 group of Keledang Loa Janan Ilir Samarinda Kindergarten have increased. From the results of observations of students' weaving activities, it can be seen that there was an increase in students in each action cycle, in cycle I with a Developing Value According to Expectations (BSH) and a percentage of 43.57% in the sufficient category, and in cycle II with a Developing Value According to Expectations (BSH) and a percentage of 87.5% in the good category